A Escola como espaço de interlocução e promoção da saúde: caminhos para educação em saúde no contexto da Região Amazônica em Santarém-Pará, Brasil - SILVA, Solange Maria de Almeida da (Universidade Federal do Oeste do Pará, 2024)
The health practices experienced by children in the family environment, supported by issues of cultural diversity, are incorporated into school life, as well as knowledge about health learned in everyday life and in formal education at school, and both can be aggregated in the various social spaces of insertion of children. This study aimed to develop health education activities in the Curucuruí Village school space, with primary school students, in order to promote health in childhood. Through the qualitative methodology of research-action, four interventions of health education were conducted, with the development of playful activities, educational games, drawings, posters, conversation circle and orientative lectures related to individual and environmental health. School is a privileged space for education and health promotion, since in this environment there is a wide interaction among children through daily exchanges, and it may be a favorable place for facing health-disease issues. Thus, the actions developed can favor the dialogue between education and health for health promotion and comprehensive care, allowing the knowledge produced in the school environment to be disseminated beyond the classroom.